An Energy Dissipative Binder for Self‐Tuning Silicon Anodes in Lithium‐Ion Batteries. Issue 2 (17th November 2022) - Tong, Yihong; Jin, Siyu; Xu, Hongyuan; Li, Jiawei; Kong, Zhao; Jin, Hong; Xu, Hui
Abstract: The volume change of the silicon anode seriously affects the electrode integrity and cycle stability. Herein, a binder, GCA13, with energy dissipation function and surface stability effect is proposed to enhance the cycle life and specific capacity. Unlike traditional binders that protect silicon electrodes through long‐chain networks, GCA13 introduces citric acid molecules with short‐range functions on the long‐chain guar gum through weak interconnection. This short‐range action is similar to the function of a spring, which can effectively buffer the silicon particle pulverization caused by the volume change. Therefore, the electrode can effectively maintain structural integration with ignorable cracks and alleviated thickness swelling. Thus, the Si@GCA13 anode exhibits a high reversible capacity of 1184 mAh g −1 under 2 A g −1 after 740 cycles with a latter coulombic efficiency of 99.9%. Extraordinarily, benefiting from the superior properties of the GCA13 binder, the electrode shows remarkable cycling stability under low (−15 and 0 °C) and high temperatures (60 °C). The work demonstrates the great potential of this binder design strategy to achieve the overall property promotion of Si anodes for practical application even under harsh service conditions. Abstract : An energy dissipative binder is designed to achieve stable cycling of Si anodes within −15–60°C. By plasticization of small molecules, this viscoelastic binder enables the electrode remarkable self‐tuning and self‐healing abilities via particle rearrangement. This binder also induces a stable bilayer solid electrolyte interphase to ensure outstanding long‐term performance of the Si anode.